Optimising Emotions, Incubating Falsehoods How to Protect the Global Civic Body from Disinformation and Misinformation - Bakir, Vian; McStay, Andrew (Springer International Publishing : Imprint: Palgrave Macmillan, 2022)
This open access book deconstructs the core features of online misinformation and disinformation. It finds that the optimisation of emotions for commercial and political gain is a primary cause of false information online. The chapters distil societal harms, evaluate solutions, and consider what must be done to strengthen societies as new biometric forms of emotion profiling emerge. Based on a rich, empirical, and interdisciplinary literature that examines multiple countries, the book will be of interest to scholars and students of Communications, Journalism, Politics, Sociology, Science and Technology Studies, and Information Science, as well as global and local policymakers and ordinary citizens interested in how to prevent the spread of false information worldwide, both now and in the future. Vian Bakir is Professor in Journalism and Political Communication at Bangor University, UK. Her most recent book is Intelligence Elites & Public Accountability: Relationships of Influence with Civil Society (2019). Andrew McStay is Professor of Digital Life at Bangor University, UK. His most recent book is Emotional AI: The Rise of Empathic Media (2018). .